Hastane hizmet kalitesi algılarında farklılaşmaya yol açan sebeplerin incelenmesi - Demir, Selma (Gebze Yüksek Teknoloji Enstitüsü, Lisansüstü Eğitim Enstitüsü, 2008)
Maliyete verilen önemin artması, değişen müşteri ihtiyaçları ve sıkı rekabet artık sağlık işletmelerinde kalitenin önemini artırmıştır. Hizmetin özünde insan sağlığı ve insana hizmet olması; kaliteli hizmeti, hasta memnuniyetini zorunlu kılmaktadır. Hasta memnuniyeti çeşitli faktörlerden etkilenen karmaşık bir kavram olup hizmet kalitesinin en önemli göstergelerindendir.Hizmette kaliteyi, hasta memnuniyetini artırmak için kişinin ihtiyaçlarına uygun hizmet vermek gerekir. Bunun için hizmet kalitesi algısındaki farklılığın sebeplerini bilmek önemlidir

Nowadays, increasing is attacted importance to cost, the changing of customer?s needs and hard competition increased importance of quality in health business. Quality service and patient satisfaction are necessary because of the existance of human health and care to human in service?s essential. Patient satisfaction is a complex concept which is affected by various factors, and it is one of the most important indicator of the service qualty. Patient?s needs convenient care is necessary for increasing patient satisfaction. Therefore it is important that know reasons of difference in the service quality perception
Investigating the differences in perception of hospital service quality
Keywords: İşletme; Business Administration